Sinergi Silang Pelaksanaan Program Kerja Malang Cerdas Baznas Kabupaten Malang Melalui Beasiswa “Satu Keluarga Satu Sarjana - Romadlon Chotib; Ulfatul Yaumi Zahro’ (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
The cross-synergy between Raden Rahmat Islamic University Malang and Baznas Malang Regency is implemented through the Malang Cerdas (Smart Malang) program. This work program aims to help children from underprivileged families continue their education, reaching children studying at various educational levels, from junior high school to higher education. Through cooperation via a Memorandum of Understanding (MoU) between Baznas Malang Regency and Raden Rahmat Islamic University Malang, this program strives to provide appropriate assistance so that these children can continue their education without obstacles. The program, named "One Family One Graduate," targets students of Raden Rahmat Islamic University Malang who are pursuing higher education and come from underprivileged families. In 2021, the "One Family One Graduate" program successfully assisted 12 students from Raden Rahmat Islamic University Malang in pursuing their education. This demonstrates that the program has been effective in helping these students continue their education.